Post a New Question

math-functions starting

posted by on .

-3f(x-4)=x^2

i have no clue what to do with the -3 in front of the f. please explain step by step as to how to do this question
the answer in the back is
-3x^2+24x-48

  • math-functions starting - ,

    The problem probably said:
    if f(x) = x^2 , find -3f(x-4)

    f(x) = x^2
    f(x-4) = (x-4)^2 = x^2 - 8x + 16
    then -3f(x-4) = 3(x^2 - 8x + 16)
    = -3x^2 + 24x - 48

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question